Academic study of Scientology: The Scientology perspective - Roux, Eric (Implicit religion, 2020)
The discussion that was conducted at the British Association for the Study of Religion (BASR) conference by the Religion Studies Project (RSP) in 2018, with David Robertson, Carole Cusack, Stephen Gregg, and Aled Thomas have raised some of the challenges that are sometimes perceived as impediments to the study of Scientology by scholars. This paper tries to approach these challenges from the point of view of the study target: The Scientologist and the Church of Scientology itself. It develops several points that could open the door to a better cooperation between scholars and Scientologists, in a time where academic interest toward this new religion is steadily increasing.